State-of-the-art and future perspectives of environmentally friendly machining using biodegradable cutting fluids - Naveed, M.; Arslan, A.; Javed, H. M. A.; Manzoor, T.; Quazi, M. M.; Imran, T.; Zulfattah, Z. M.; Khurram, M.; Fattah, I. M. R. (MDPI AG, 2021)
The use of cutting fluids has played a vital role in machining operations in lubrication and cooling. Most cutting fluids are mineral oil-based products that are hazardous to the environment and the worker, cause severe diseases and pollute the environment. In addition, petroleum resources are becoming increasingly unsustainable. Due to environmental and health issues, legislations have been established to ensure that the consumption of mineral oil is reduced. Consequently, researchers are making efforts to replace these mineral oil-based products. Vegetable oils are grasping attention due to their better lubricating properties, ease of availability, biodegradability, low prices, and non-toxicity. In this study, a detailed review and critical analysis are conducted of the research works involving vegetable oils as cutting fluids keeping in view the shortcomings and possible solutions to overcome these drawbacks. The purpose of the review is to emphasise the benefits of vegetable oil-based cutting fluids exhibiting comparable performance to that of mineral oil-based products. In addition, an appropriate selection of non-edible vegetable oil-based cutting fluids along with optimum cutting parameters to avoid a scanty supply of edible oils is also discussed. According to this research, vegetable oils are capable of substituting synthetic cutting fluids, and this option might aid in the successful and cost-efficient implementation of green machining.